Down-regulation of miR-19b-3p enhances IGF-1 expression to induce osteoblast differentiation and improve osteoporosis - Yu, Yifan; Cai, Wei; Xu, Yong; Zuo, Wenshan (Cellular and Molecular Biology, 2022)
This research was conducted in order to investigate the role of miR-19b-3p in the development of osteoporosis (OP) in rats and the associated mechanisms. This study measured the expression levels of miR-19b-3p and IGF-1 in clinical OP patients and ovariectomy-induced OP rats by qRT-PCR. The osteoprotegerin levels in OP patients were measured by enzyme-linked immunosorbent assay (ELISA). The binding site of miR-19b-3p to IGF-1 was predicted by three prediction sites: Target Scan, miRDB and starbase. Experiments were conducted in vitro and in vivo using bone marrow mesenchymal stem cells (BMSCs) and OP rats, respectively, to verify the regulatory relationship between miR-19b-3p and IGF-1 and explore the role of miR-19b-3p in the development of OP. Results showed that the expression of miR-19b-3p was elevated in OP patients and rats, while IGF-1 expression was decreased (***p<0.001). The ELISA assay found that osteoprotegerin levels were inversely correlated with miR-19b-3p and positively correlated with IGF-1. The predictive analysis identified binding sites for miR-19b-3p to IGF-1. The potential regulatory relationship between miR-19b-3p and IGF-1 was validated by in vitro and in vivo experiments. Moreover, the important role of miR-19b-3p in the regulation of OP was further demonstrated. It was concluded the inhibition of miR-19b-3p has a suppressive effect on the development of OP and the function of miR-19b-3p in OP is likely to be achieved by regulating the expression of the IGF-1 gene.